SKRINING FITOKIMIA DAUN KATUK ( Sauropus androgynus ) SEBAGAI PELANCAR ASI - Syhadat, Anwar; Siregar, Nurelilasari (Jurnal Kesehatan Ilmiah Aufa Royhan, 2020)
Katuk leaves (Sauropus androgynus (L.) Merr.) Have been shown to have a variety of activities pharmacology. Chemical content contained in katuk leaves which plays a role in giving the pharmacological activity. Phytochemical screening aims to provide a description of the group compounds contained in plants that are being studied. Phytochemical screening carried out on katuk leaves (Sauropus androgynus (L.) Merr.) Includes examination of alkaloids, steroids / triterpenoids, saponins, tannins, polyphenols, glycosides and flavonoids. Phytochemical screening test results showed that 90% ethanol extract of katuk (Sauropus androgynus (L.) Merr.) Leaves positively contained alkaloid, triterpenoid, saponin, tannin, polyphenol, glycoside and flavonoid compounds. Keywords: Katuk leaves, Breastfeeding Smoothing and Phytochemical Screening